2013
DOI: 10.1039/c3lc50447f
|View full text |Cite
|
Sign up to set email alerts
|

Single particle detection, manipulation and analysis with resonant optical trapping in photonic crystals

Abstract: We demonstrate a resonant optical trapping mechanism based on two-dimensional hollow photonic crystal cavities. This approach benefits simultaneously from the resonant nature and unprecedented field overlap with the trapped specimen. The photonic crystal structures are implemented in a 30 mm 6 12 mm optofluidic chip consisting of a patterned silicon substrate and an ultrathin microfluidic membrane for particle injection and control. Firstly, we demonstrate permanent trapping of single 250 and 500 nm-sized part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…11,12 The results in these papers were obtained using a thin PDMS-only microfluidic membrane. The control of the flow inside the microfluidic channel is important for this application, since the measurements have to be in a stable environment.…”
Section: Application To Optical Trapping and Integrated Photonic Crysmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 The results in these papers were obtained using a thin PDMS-only microfluidic membrane. The control of the flow inside the microfluidic channel is important for this application, since the measurements have to be in a stable environment.…”
Section: Application To Optical Trapping and Integrated Photonic Crysmentioning
confidence: 99%
“…11,12 Trapping a polystyrene sphere of 500 nm diameter is more efficient with the hybrid microfluidic than with the PDMS-only microfluidic. This is demonstrated when plotting the centroid of the position of the center of emission of a nanoparticle of 500 nm in polystyrene trapped with the same amount of power in both case in Fig.…”
Section: Application To Optical Trapping and Integrated Photonic Crysmentioning
confidence: 99%
“…For instance, Descharmes et al [85,86] reported single particle detection using a PC waveguide cavity with a single large point defect in a hexagonal lattice (Figure 3a). In their experimental setup, it is possible to record large dynamic changes in the power transmitted through the device, while the particle traverses the PC waveguide cavity, as can be observed in Figure 3b.…”
Section: Waveguide Defectmentioning
confidence: 99%
“…By employing this mechanism, the PhC cavity enabled the detection of target materials, such as gases, 16 particles, 17 viruses, 18 and biomolecules, 6,19 with an ultrahigh sensitivity according to the structural and surrounding refractive-index changes within a fractional sample volume. Considering its sensitivity and device size (~10 μm), the PhC cavity is promising for the development of microscale optical sensors compared with other technologies, such as surface plasmon resonance, optical waveguides, and ring resonators.…”
Section: Introductionmentioning
confidence: 99%